Regional impacts of climate change on agriculture and the role of adaptation - Berry, P.; Ramírez Villegas, Julián Armando; Bramley, H.; Mgonja, MA; Mohanty, S (CAB International, 2014)
This chapter discusses the impacts of climate change on agriculture and the role of adaptation. Specifically, the chapter explores the following impacts of climate change on agriculture: increased CO2 concentrations, water availability, and pests and diseases. The chapter also includes reports of case studies on climate change impacts on wheat, rice and millet.